Adherence To Practice Guidelines For Erector Spinae Plane Block-Catheter Based Analgesia In Thoracic Surgery Patients - Ur Rehman, Sami; Qamar, Naila; Kashif, Aleena; Basri, Rabia; Saeed, Unaiza; Rehman, Eesha (Biological and Clinical Sciences Research Journal, 2025)
In thoracic surgery, effective postoperative pain management is crucial to enhance recovery and reduce complications. Erector spinae plane block (ESPB) has gained recognition as a promising regional analgesic technique due to its safety, ease of administration, and minimal complications. However, variations in its utilisation, catheter placement techniques, local anesthetic concentrations, and infusion rates remain an area of clinical interest. Objective: This study aims to scrutinise the utilisation of ESPB-catheter based analgesia practice in thoracic surgery patients, techniques, complications and different concentrations and volumes of local anesthetics used for pain relief.Study design: Clinical practice article/Clinical Audit. Study Place and Duration: 2.5 years from 1st January 2022 to 30th June 2024 in Doctors Hospital and Medical Centre (DHMC) operation theatres, Lahore, Pakistan. Methodology: A total of 76 patients were included in the study. All captured data was recorded manually and then presented as frequencies (percentages) in Microsoft Word Office 365 tabulated form. All calculations were done manually. Results: 76 erector spinae plane block related catheters were inserted in thoracic surgery patients. Tuohy’s needle was used for ESPB. Mean needle depth was 5cm and mean catheter depth was 11cm. Different concentrations of local anesthetics were used (0.1%, 0.2% and 0.25%) at different infusion rates (10ml/hour up to 20ml/hour). No complication was encountered during our study period. Conclusion: Erector Spinae Plane Block provides the best pain relief with minimum complication risks and maximum postoperative benefits, including its use in patients with coagulopathy and systemic infections. So, ESPB catheter-based analgesia with continuous infusion (0.15 or 0.2% bupivacaine at 15-20ml/hour) should be the preferred mode of postoperative analgesia after thoracic surgery. The catheter can be kept for a maximum of 6 days. Hence, a collaborative approach is required between the thoracic surgeon and the anesthetist.